Pulsed-Bed Column Adsorption for Triclosan Removal Using Macadamia Nut Shell Activated Carbon - Jareeya Yimrattanabovorn; Mananya Phalaiphai; Siriwan Nawong (Salehan Institute of Higher Education, 2024)
Triclosan (TCS), a common antibacterial agent found in numerous personal care products, has been detected in wastewater and surface water and is now of significant environmental concern due to its health impacts. To mitigate this issue, various treatment methods have been explored. This study investigated the efficacy of Macadamia nut shell activated carbon (MAC) as an economical adsorbent for triclosan removal. A pulsed-bed column adsorption technique was applied to enhance adsorption capacity and prolong the operational lifespan of the column. Batch experiments were conducted to explore various parameters and adsorption capacity. Column experiments were carried out to investigate breakthrough curves and various associated parameters. In batch experiments, MAC exhibited a high TCS adsorption capacity of 119.05 mg/g, and optimal adsorption conditions were determined. Adsorption kinetics followed the pseudo-second-order model, and equilibrium data were well-fitted by both the Langmuir and Freundlich isotherm models. A pulsed-bed column adsorption showed superior performance compared to a fixed-bed column under specific conditions (flow rate: 10 mL/min, TCS initial concentration: 60 mg/L, bed column height: 10 cm) and removal bed height of only 6 cm, successfully enhancing TCS adsorption capacity to 53.40 mg/g and extending the operational lifespan of the column to 5,280 minutes. Adapting pulsed-bed columns for TCS removal from wastewater in the personal care product industry led to the extension of column life with increased adsorption capacity and minimized the use of adsorbents as a practical and environmentally friendly method. Doi: 10.28991/CEJ-2024-010-05-019 Full Text: PDF